Fragile and conflict affected situations and small island developing states approach. (Manila Asian Development Bank, 2021)
As this paper explains, the FSA introduces flexible processes and procedures that will allow ADB to tailor interventions to the specific challenges of developing member countries, with the goal of improving project results, and ultimately improving livelihoods. FCAS and SIDS face unique development challenges such as a greater need for governance and institutional capacity building, geographic isolation, small populations, narrow asset bases, and armed conflict.
Keywords: Civil society -- Developing countries; Social groups -- Developing countries; Social planning -- Developing countries; Social stratification -- Developing countries; Electronic books